A Novel DNA Methyltransferase Dnmt3a3 Splice Variant Represses Preadipocyte Proliferation and Differentiation - Abdalla, Bahareldin Ali; Li, Zhenhui; Nie, Qinghua (Frontiers in Genetics, 2020)
Proliferation and differentiation of preadipocyte are essential for the formation of fat tissues. However, the genes that regulate the early stage of preadipocyte differentiation in chicken have remained elusive. Here we identify a novel spliced variant of the DNA methyltransferase Dnmt3a gene, named Dnmt3a3, that controls early preadipocyte differentiation. Dnmt3a3 expression is increased at the onset of preadipocyte differentiation and remains elevated during differentiation. Overexpression of Dnmt3a3 in preadipocytes markedly inhibits proliferation and cell-cycle progression, and this is accompanied by inhibition of the mRNA and protein level of cell-cycle control genes, such as p21 and p27. In addition, forced expression of Dnmt3a3 in differentiating preadipocytes represses early preadipocyte differentiation, and this was found to be accompanied by inhibition of the mRNA expression levels of early preadipocyte differentiation markers, such as GATA2, GATA3, C/EBPα, C/EBPβ, AP2, and PPARγ, or the protein levels of GATA3, C/EBPβ and PPARγ. Taken together, these data demonstrate the participation of Dnmt3a3 in the proliferation and differentiation process of chicken primary preadipocyte cells.